2005
DOI: 10.1124/mol.105.012807
|View full text |Cite
|
Sign up to set email alerts
|

The Gln4863Ala Mutation within a Putative, Pore-Lining Trans-Membrane Helix of the Cardiac Ryanodine Receptor Channel Alters Both the Kinetics of Ryanoid Interaction and the Subsequent Fractional Conductance

Abstract: The specific, high-affinity interaction of the plant toxin ryanodine with its molecular target the ryanodine receptor channel (RyR) has been instrumental in RyR research. Alanine scanning of putative pore regions of mouse RyR2 has highlighted the amino acid Gln4863, predicted to lie within trans-membrane helix TM10, as an important determinant of ryanodine binding. We have investigated the effects of several ryanodine derivatives, guanidinopropionylryanodine, 21-p-nitrobenzoylamino-9␣-hydroxyryanodine, 8␤-amin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…For example, both Leishmania homologues and the S. mansoni IP 3 R-like homologue differ from human IP 3 Rs/RyRs near the selectivity filter region, at positions analogous to hRyR1 residues G4891 and R4893 that are known to affect ryanodine binding [24]. Also, all parasite homologues (except the S. mansoni RyR homologue) differ from human RyRs in the pore-lining transmembrane domain, at the position analogous to Q4934 of hRyR1, which is a determinant of ryanodine binding [25]. Some pathogenic parasites therefore possess homologues of both IP 3 Rs and RyRs in which key functional domains are well enough conserved to suggest that these proteins might function as intracellular Ca 2+ channels.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…For example, both Leishmania homologues and the S. mansoni IP 3 R-like homologue differ from human IP 3 Rs/RyRs near the selectivity filter region, at positions analogous to hRyR1 residues G4891 and R4893 that are known to affect ryanodine binding [24]. Also, all parasite homologues (except the S. mansoni RyR homologue) differ from human RyRs in the pore-lining transmembrane domain, at the position analogous to Q4934 of hRyR1, which is a determinant of ryanodine binding [25]. Some pathogenic parasites therefore possess homologues of both IP 3 Rs and RyRs in which key functional domains are well enough conserved to suggest that these proteins might function as intracellular Ca 2+ channels.…”
Section: Resultsmentioning
confidence: 98%
“…the ion-conducting pore region) exist, such as those shown to exist between human and parasite IP 3 R/RyR homologues ( Figure 1 ). As pharmacological blockers of IP 3 Rs and RyRs such as xestospongin-C and ryanodine are thought to bind within the pore region [24], [25], [117], this sequence divergence suggests the possibility of developing drugs with specificity for parasite homologues. Experimental observations also suggest the possibility for drug selectivity.…”
Section: Discussionmentioning
confidence: 99%
“…Studies using recombinant mouse RyR2 have demonstrated that mutation of residues in this helix influences the interaction of both blocking molecules (20) and ryanodine (21, 22) with the channel and can modify the response to activating ligands (23). Importantly, the RyR2 PFR model also identifies a sequence of residues in TM10 (G 4864 LIIDA 4869 ) that is equivalent to the G XXXX A hinge motif identified in K + channels (4), and this hinge motif is also present in RyR1 TM10 (5, 6).…”
Section: Introductionmentioning
confidence: 99%
“…If the ryanoid binding site is within the pore, a more probable site of interaction may be provided by the inner helices that line the cytosolic cavity of the pore in the open channel (Welch et al, 2004). Indeed, mutation of residues within this helix can result in significant reduction in the ability of RyR to bind ryanodine and other ryanoids (Wang et al, 2003;Ranatunga et al, 2005). The enormous rates of permeant ion movement achieved in RyR indicate that the channel must have a large capture radius; as a consequence, it is probable that the cytosolic cavity of the pore will be much wider than the constricted region within which TEA ϩ blocks K ϩ translocation, with the voltage drop across the channel extending some way into this cavity .…”
Section: Discussionmentioning
confidence: 99%
“…Point mutation of various residues within the pore forming region of the RyR produced alterations in the interaction of both [ 3 H]ryanodine with populations of receptors and ryanoids with single channels, without altering other characteristics of channel function (Chen et al, 2002;Wang et al, 2003;Ranatunga et al, 2005). Consistent with a location of the high-affinity ryanoid binding site within the pore of the RyR channel, [ 3 H]ryanodine binding studies and single channel experiments have established that ryanodine binds preferentially to the open conformation (Chu et al, 1990;Meissner and El-Hashem, 1992;Tanna et al, 1998) and that the site is only available from the cytosolic face of the channel (Tanna et al, 1998).…”
mentioning
confidence: 99%